Groundwater governance for improving city water resilience in Cape Town, South Africa - Faragher, Tamsin P. T.; Carden, Kirsty (Frontiers in Sustainable Cities, 2023)
Until recently, Cape Town, South Africa’s second largest city relied entirely on surface water for water supply. Low rainfall between 2015 and 2018 caused extreme water scarcity and water insecurity, even though the city is located on a number of significant aquifers. Water demand management measures instituted during the drought accelerated the transition to a decentralised, hybrid system. Groundwater played an important role in this transition, particularly for households, the bulk users of utility-supplied water. The current water governance and management is ill-equipped for the emergent hybrid system underpinned by an engineering approach that treats water narrowly as a resource for supply and use. This approach is problematic because it does not adequately consider water as one of multiple systems comprising the environment that supplies critical eco-services. Even though the City of Cape Town does not believe it has a groundwater management role, its responsibilities for water and sanitation services, spatial planning, land-use management and environmental management - intersect with groundwater management. Significant water governance reform is therefore necessary for sustainable groundwater use and resilience in Cape Town and other South African cities.